Evaluating NATO enlargement from Cold War victory to the Russia-Ukraine war (Switzerland, Palgrave Macmillan, Cham, 2023)
Mobilizing an interdisciplinary group of scholars and practitioners, this book reviews the history and consequences of NATOs post-Cold War enlargement into Central and Eastern Europe. It offers a nuanced discussion of the merits and drawbacks of NATO enlargement across the different actors involved and compares the results of the policy against potential alternatives that were not chosen. Particular attention is given to NATO enlargements influence on the course of U.S. foreign policy, democracy and security in Central and Eastern Europe, NATOs own development as a political and military institution, and relations with China and Russia (including the 2022 Russia-Ukraine War). Written for an engaged audience, the book is designed to appeal to students, researchers, and policymakers alike while offering both policy insights and avenues for future scholarship. James Goldgeier is Visiting Scholar at Stanford Universitys Center for International Security and Cooperation, Visiting Fellow at the Brookings Institution, and Professor of International Relations at the School of International Service at American University, where he served as Dean from 201117. Joshua R. Itzkowitz Shifrinson is Associate Professor with the School of Public Policy at the University of Maryland, Senior Fellow with the Center for International and Security Studies at Maryland (CISSM), and Associate Editor of H-Diplos International Security Studies Forum (ISSF)
Keywords: Print books